MuBaBaO: Bridging the Gap between Human and Artificial Intelligence - Ramya, Rachita (Roczniki Kulturoznawcze, 2024)
This paper explores the applications of MuBaBaO Creative Thinking Blocks as an educational tool in the artificial intelligence-driven era. The multidimensional MuBaBaO method diverges from traditional learning methods and emphasizes fostering critical thinking, effective communication, creativity, spatial and emotional intelligence through non-linear pedagogy. By engaging participants in creative and problem-solving tasks using wooden blocks, this dynamic exploratory approach enhances cognitive abilities and prepares students to thrive alongside AI advancements. The paper highlights the importance of developing distinctive human qualities and skills, such as adaptability, imagination, and innovative thinking, to complement the technical knowledge required in a technology-dominated landscape.